2011
DOI: 10.1002/mop.26017
|View full text |Cite
|
Sign up to set email alerts
|

Simple printed monopole slot antenna for penta‐band wireless wide area network operation in the mobile handset

Abstract: A simple printed monopole slot antenna for penta-band wireless wide area network operation (824-960/1710(824-960/ -2170 in the mobile handset is presented. The monopole slot has a length of 50 mm only and is embedded close to the bottom edge of the system ground plane of the handset with a small distance of 11 mm. By adding a smallsize C-shaped strip connected orthogonal to the bottom edge of the system ground plane, good excitation of the monopole slot antenna at its fundamental (0.25 wavelength) and higher-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Therefore, a 4-antenna L-shaped monopole slot array is further proposed in this work. The concept of monopole slot antenna design is stemmed from a patent reported in [23], and its merits as reported in [24][25][26] have shown that this design is very suitable for mobile handset designs.…”
Section: B L-shaped Monopole Slot Arraymentioning
confidence: 99%
“…Therefore, a 4-antenna L-shaped monopole slot array is further proposed in this work. The concept of monopole slot antenna design is stemmed from a patent reported in [23], and its merits as reported in [24][25][26] have shown that this design is very suitable for mobile handset designs.…”
Section: B L-shaped Monopole Slot Arraymentioning
confidence: 99%
“…. Compared with antennas with metal strips or frames, the proposed antenna has lower height and smaller size. Compared with reconfigurable antennas using diodes, no DC bias voltage is required in the proposed antenna.…”
Section: Mobile Phone Antenna Configuration Analysis and Measurementmentioning
confidence: 99%
“…There are some literatures published on mobile phone antennas of printed slot type mainly with rectangular shaped slot . However, none of the above comes from UWB configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The internal antennas for mobile devices such as handsets, laptop computers and table computers operating at GSM850/900/1800/1900/UMTS (824 ~ 896/880 ~ 960/1710 ~ 1800/1850 ~ 1990/1920 ~ 2170 MHz) bands have been presented [1][2][3][4][5][6][7][8][9]. Owing to the LTE (long term evolution) operation, which is recently introduced to provide much higher data rate than the WWAN operation, mainly includes three operating bands in the LTE700 (698 ~ 787 MHz), LTE2300 (2300 ~ 2400 MHz) and LTE2500 (2500 ~ 2690 MHz).…”
Section: Introductionmentioning
confidence: 99%